Pragmatic Use of Catheter-Directed Thrombolysis in Venous Thromboembolism and a Comparative Evaluation With Traditional Therapies in Submassive Pulmonary Embolism. (October 2022) - Bradley, Mary; Bull, Todd; Hountras, Peter; MacLaren, Robert
Background: Catheter-directed thrombolysis (CDT) is a novel treatment for venous thromboembolism (VTE). Limited data describe pragmatic use of CDT and compare CDT to other VTE therapies. Objective: Assess the use of CDT and comparatively evaluate CDT, anticoagulation, and systemic thrombolysis in submassive pulmonary embolism (PE). Methods: Retrospective, single-center, chart audit. Part 1 described all patients who received CDT for VTE. Part 2 matched patients with submassive PE who received CDT, heparin, or systemic thrombolysis and assessed length of stay (LOS), bleeding, all cause in-hospital mortality, and escalation of care. Results: For part 1, 70 CDT patients were identified; 42 with DVT and 28 with PE. ICU LOS was longer (2.5 ± 2.9 vs. 4.9 ± 8.4 days, p = 0.07), escalation of care more frequent (0% vs. 35.7%, p < 0.0001), and hospital mortality greater (2.4% vs. 21.4%, p = 0.014) in the PE group. For part 2, 21 CDT patients were matched to 21 heparin and 21 systemic thrombolysis patients. All CDT and tPA patients were admitted to the ICU versus only 6 (28.6%, p < 0.001) heparin patients. ICU LOS was significantly longer in the CDT group versus systemic tPA and systemic anticoagulation (80.7 ± 64.1 vs. 48.2 ± 27.7 vs. 24.9 ± 59.1 hours; p = 0.0048). More IVC filters and thrombectomies were performed in the CDT group. Conclusions: CDT is frequently used for both DVT and PE and requires ICU admission. Escalation of care is common when CDT is used for PE. For submassive PE, CDT is associated with prolonged ICU LOS compared to heparin or systemic thrombolysis. Resource utilization with CDT requires further evaluation.